Peace in Ancient Egypt. - Vanessa Davies (Harvard Egyptological Studies, 2018)
One of the world's oldest treaties provides the backdrop for a new analysis of the Egyptian concept of hetep (\'peace\'). To understand the full range of meaning of hetep , Peace in Ancient Egypt explores battles against Egypt's enemies, royal offerings to deities, and rituals of communing with the dead. Vanessa Davies argues that hetep is the result of action that is just, true, and in accord with right order ( maat ). Central to the concept of hetep are the issues of rhetoric and community. Beyond detailing the ancient Egyptian concept of hetep , it is hoped that this book will provide a useful framework that can be considered in relation to concepts of peace in other cultures.